Antimicrobial laser-activated sealants for combating surgical site infections. (20th April 2021) - Urie, Russell; McBride, Michelle; Ghosh, Deepanjan; Fattahi, Ali; Nitiyanandan, Rajeshwar; Popovich, John; Heys, Jeffrey J.; Kilbourne, Jacquelyn; Haydel, Shelley E.; Rege, Kaushal
Abstract : Antibiotic-loaded laser-activated sealants (LASEs) combat surgical site infections (SSIs) by facilitating the rapid closure of tissues, formation of a physical barrier, and antibacterial activity at the wound site. Abstract : Surgical-site infections (SSIs) occur in 2–5% of patients undergoing surgery in the US alone, impacting 300 000–500 000 lives each year, and presenting up to 11 times greater risk of death compared to patients without SSIs. The most common cause of SSI is Staphylococcus aureus, and methicillin-resistant S. aureus (MRSA) is the most common pathogen in community hospitals. Current clinical devices used for approximating incisions and traumatic lacerations include sutures, adhesives, tapes, or staples with or without antimicrobial incorporation. However, current closure technologies may not provide adequate protection against infection, are susceptible to wound dehiscence, and can result in delayed biomechanical recoveries. Laser-activated tissue repair is a sutureless technique in which chromophore-loaded sealants convert laser light energy to heat in order to induce rapid tissue sealing. Here, we describe the generation and evaluation of laser-activated sealant (LASE) biomaterials, in which, indocyanine green (ICG), an FDA-approved dye, was embedded in a silk fibroin matrix and cast into films as wound sealants. Silk-ICG films were subjected to different near-infrared (NIR) laser powers to identify temperatures optimal for laser sealing of soft tissues. A mathematical model was developed in order to determine the photothermal conversion efficiency of LASEs following laser irradiation. NIR laser activation of silk-ICG LASEs increased the recovery of skin biomechanical strength compared to sutured skin in full-thickness incisional wounds in immunocompetent mice, and live animal imaging indicated persistence of silk-ICG LASEs over several days. LASEs loaded with the antibiotic vancomycin demonstrated higher efficacies for combating MRSA infections in a mouse model of surgical site infection compared to antibacterial sutures. Our results demonstrate that LASEs can be loaded with antimicrobial drugs and may serve as new multifunctional biomaterials for rapid tissue sealing, repair and surgical site protection following surgery.